Regionally nested patterns of fish assemblages in floodplain lakes of the Magdalena river (Colombia) (2012)
ABSTRACT: We investigated if fish assemblages in neotropical floodplain lakes (cienagas) exhibit nestedness, and thus offer support to the managers of natural resources of the area for their decision making. The location was floodplain lakes of the middle section of the Magdalena river, Colombia. We applied the nested subset analysis for the series of 30 cienagas (27 connected to the main river and three isolated). All fish were identified taxonomically in the field and the matrix for presence–absence in all the lakes was used for the study of the pattern of nestedness. The most diverse order was Characiformes (20 species), followed by Siluriformes (19 species). Characidae and Loricaridae were the richest families. The species found in all the lakes studied were migratory species (17), and sedentary species (33). Two species (Caquetaia kraussii and Cyphocharax magdalenae) were widespread across the cienagas archipelago (100% of incidence). Nestedness analysis showed that the distribution of species over the spatial gradient studied (840 km) is significantly nested. The cienagas deemed the most hospitable were Simiti, El Llanito, and Canaletal. Roughly, 13 out of the 50 species caught show markedly idiosyncratic distributions. The resulting dataset showed a strong pattern of nestedness in the distribution of Magdalenese fishes, and differed significantly from random species assemblages. Out of all the measurements taken in the cienagas, only the size (area) and local richness are significantly related to the range of order of nested subset patterns (r = –0.59 and –0.90, respectively, at p < 0.01). Differential species extinction is suggested as the cause of a nested species assemblage, when the reorganized matrix of species occurring in habitat islands is correlated with the island area. Our results are consistent with this hypothesis.